The Impact of BNM Guidelines on Household Loans on Commercial Bank and Islamic Bank Performances - Isa, Mohamad Yazid; Mohd Hussin, Mohd Yahya (Human Resource Management Academic Research Society, 2016)
This paper aims to analyze the impact of BNM guidelines on household loans on Malaysian bank performances. This paper employs panel data analysis which covers 24 banks (12 commercial banks and 12 Islamic banks) and the data consists of bank specific variables, household loans and other macroeconomic variables for the period of 2004-2015. The results reveal that household loans have significant impact on bank performance. Any policy implemented by government in controlling household loans should be imposed carefully because it will give impact to the banking industry and economic growth of the country